Study of the Use of the Rules of al Masyaqqatu Tajlibu al Taisir in DSN Fatwa No. 67 of 2008 concerning Sharia Factoring - Ismatul Maula (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This study aims to examine more deeply the use of the al-Masyaqqatu Tajlibu al-Taisir rule as a tool to explore Islamic law in determining contemporary problems. The National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as a forum that produces fatwas on Islamic law in Indonesia uses this rule as one of the arguments for the birth of sharia factoring law. However, what is the use of this rule to determine a sharia factoring fatwa by the National Sharia Council, as well as whether the significance of this rule in determining the fatwa is in accordance with the concept and understanding. This research is a normative juridical research so that what is examined is the legal basis and rules used by the National Sharia Council with a conceptual approach that analyzes the use of the al-Masyaqqatu Tajlibu al-Taisir rule in determining the fatwa on factoring so that it can be understood and the acquisition of proper understanding regarding these concepts. The data obtained is data from the library and then analyzed descriptively. The research results obtained are that the use of the rule al masyaqqatu tajlbu al taisir as the basis for the istinbat fatwa of the National Sharia Council Number 67 of 2008 Islamic factoring does not show its urgency conceptually. There is a blurring of terms that fiqh needs to be clarified in accordance with sharia provisions. Where these rules conceptually explain how the shari'a allows one difficulty to be avoided in order to achieve convenience that eliminates distress, danger or encouragement of urgent needs. Factoring conceptually describes the activities of financial institutions in terms of the transfer and sale of receivables which fiqh has the term bai dain where the Ulama only allow the sale of debt only to madin (who owes money), the use of wakalah bi ujroh contracts and the withdrawal of qard contracts as bailouts in fatwa The DSN MUI has a gap of understanding that is different from the concept of hawalah in fiiqh and also in Bank Indonesia regulations. There is an imbalance in terms and understanding regarding the use of these rules as well as wakalah bi ujrah, qard and hawalah contracts.